2018
DOI: 10.1002/jctb.5693
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of extractive distillation separation sequences for acetonitrile/methanol/benzene multi‐azeotropic mixtures

Abstract: Background The extractive distillation‐based separation of a multi‐azeotropic mixture has several optional solvents and schemes. The screen of a suitable solvent was performed and diverse extractive distillation sequences were compared for separating the specified mixture of acetonitrile/methanol/benzene. Result As a solvent breaking all binary azeotropes, chlorobenzene was selected over aniline on the basis vapor–liquid equilibrium diagrams and infinite dilution factors. Four separation sequences were optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…However, the mixture must be handled properly in order to avoid waste of resources and environmental pollution. Conventional distillation is unable to effectively separate this system due to the presence of three binary azeotropes, and thus some special separation methods must be considered . Recently, a few studies have been reported for the separation of the THF–ethanol–water system via extractive distillation and PSD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mixture must be handled properly in order to avoid waste of resources and environmental pollution. Conventional distillation is unable to effectively separate this system due to the presence of three binary azeotropes, and thus some special separation methods must be considered . Recently, a few studies have been reported for the separation of the THF–ethanol–water system via extractive distillation and PSD.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional distillation is unable to effectively separate this system due to the presence of three binary azeotropes, and thus some special separation methods must be considered. [16][17][18] Recently, a few studies have been reported for the separation of the THF-ethanol-water system via extractive distillation and PSD. Zhao et al 19,20 investigated the steady state design of conventional and thermally coupled extractive distillation configurations with various extracting agents.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al proposed a method for identifying the optimal solvent on the basis of isovolatility curves [3]. Based on vaporliquid equilibrium diagrams and infinite dilution factors, Wang et al selected the feasible solvent to separate the specified mixture and targeted the optimal distillation sequence with minimum TAC [4]. In view of controllability and economy, Wang et al simulated two possible extractive distillation sequences for separating toluene-methanol-water ternary azeotropic mixture to identify suitable flowrate of solvent [5].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of the solvent is to enhance the relative volatility of azeotropic mixtures. [5][6][7] An appropriate solvent possesses not only high solubility but also high selectivity to the separated mixture. Usually, for extractive distillation, there are three kinds of solvent, namely organic solvent, 8 inorganic salt 9 or mixtures of inorganic salt and organic solvent.…”
Section: Introductionmentioning
confidence: 99%
“…In the circumstances, extractive distillation which is usually used to separate azeotropic mixtures or close‐boiling mixtures was adopted by adding an appropriate solvent. The addition of the solvent is to enhance the relative volatility of azeotropic mixtures 5–7 . An appropriate solvent possesses not only high solubility but also high selectivity to the separated mixture.…”
Section: Introductionmentioning
confidence: 99%